Low intensity gamma-frequency TMS safely modulates gamma oscillations in probable mild Alzheimer’s dementia: a randomized 2 × 2 crossover pilot study - Mimenza-Alvarado, A. J.; Aguilar-Navarro, S. G.; Abarca-Jiménez, I. E.; Vázquez-Villaseñor, I.; Luna-Umanzor, Diana I.; Dorard, C.; Villafuerte, G. (Frontiers in Neurology, 2025)
IntroductionAD is a progressive neurodegenerative disorder characterized by cognitive decline and memory loss. While traditional treatments targeting beta-amyloid accumulation have shown limited success, there is a pressing need for novel therapeutic approaches. Recent studies have highlighted the role of disrupted gamma oscillations in AD pathology, leading to the exploration of gamma neuromodulation as a potential therapeutic strategy to modify disease progression in individuals with AD dementia. This pilot clinical trial aimed to investigate the electrophysiological effects of low intensity gamma transcranial magnetic stimulation (gTMS) on gamma oscillations in patients with a diagnosis of probable mild AD dementia.MethodsEmploying a randomized, double-blind, sham-controlled, 2 × 2 crossover design, participants underwent a single session of both real low intensity gTMS and sham stimulation. EEG recordings and cognitive assessments were conducted before and after stimulation to assess changes in brain activity and their impact on episodic memory.ResultsWe observed statistically significant changes in EEG activity (n = 14), indicating transient modulation of gamma oscillations immediately after low intensity gTMS. There was no significant improvement in cognition compared to baseline scores, but we evidenced a positive correlation between electrophysiological changes and cognitive outcome. Importantly, the intervention was well-tolerated, with no significant adverse effects reported.DiscussionLow intensity gTMS has shown the capability to induce significant changes in brain activity, particularly in gamma oscillations. These findings suggest that low intensity gTMS holds promise as a safe and non-invasive therapeutic approach, challenging the conventional belief that high intensity magnetic pulses are necessary for effective brain modulation. To corroborate these initial findings, further research with extended intervention durations and larger, well-defined cohorts of patients with mild AD dementia is essential. This will validate the potential benefits of low intensity gTMS on cognitive performance in this population.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT05784298?term=NCT05784298&rank=1, NCT05784298.